Effectiveness of Educational Games in Improving Students’ Cognitive and Social Skills - Abidin, Dindin (Al-Hijr: Journal of Adulearn World, 2023)
Cognitive ability is an inner skill that uses the brain that is needed to perform tasks or anything that is simple to the most complex tasks. Games in education for students will help them develop the ability of cognitive structures in themselves, with the development of cognitive skills, students will also foster social attitudes in themselves and will help them socialize in society. The purpose of this study is to examine the effectiveness of educational games in improving students’ cognitive and social skills. This research was conducted to understand that educational games can improve students’ cognitive skills and can also develop students’ social attitudes, while this research will also illustrate whether these educational games can be applied to all levels of education in schools. The method used in this study is a quantitative method in which in this case, the data collection used is by means of a questionnaire, with the correlation method to be applied through SPSS statistical software. Respondents involved in this study are students who are currently studying elementary school education and the results of the preparation of students who are used as assessment materials. The results obtained from this study explain that the effectiveness of educational games in improving students’ cognitive and social skills has a good impact on students who are taking elementary school education, educators can also find out the effectiveness of educational games in improving students’ cognitive and social skills. The conclusion obtained from this research outlines the effectiveness of educational games in improving the cognitive and social skills of students who are still studying in elementary school. With educational games can also find out the cognitive skills possessed by students and can also find out their attitudes in their social environment. Educational games can also develop students’ cognitive and social attitudes.